Syntheses and structures of a new class of aza- and thio-ether macrocyclic d(0) imido complexes - Wilson, P; Blake, A; Mountford, P; Schroder, M (1998)
The synthesis and structures of a family of macrocyclic, d0 titanium imido complexes [Ti(NBut)(L)Cl2] (L = [9]aneN3, Me3[9]aneN3, [9]aneS3 or Me2[9]aneN2S) are reported; the new compounds are isolobal analogues of group 4 metallocene dichlorides.